Sustainable Construction: Material Onsite Management - Ariffin, Anita (Universiti Sains Malaysia, 2006)
The concept of sustainable construction and the definition also can be described as “subset of sustainable development to the construction industry. It encompasses issues such life cycle, procurement, site planning and organization, material selection, reuse, recycle, waste and energy minimization.” The direct relationship between sustainable development and construction industry is obvious as construction is the engine of development. Perhaps sustaining development is more appropriate to be considered along the lines of sustaining construction. This is so as construction are both business and technical in nature. Thus the industry is very much a business and economic concern, whilst the technical matters relates to the mechanics of delivering the business. So if the sustainable development is literally taken as constraining development, it connotes a negative impact to the industry.